FAKTOR-FAKTOR YANG MEMPENGARUHI TOTAL PENERIMAAN PAJAK NEGARA DAN EFEKTIFITAS PERATURAN PERPAJAKAN - Wahyu Kartika Wijayanti; Agus Bagus Budi N (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
This research aims to analyze and gain empirical evidences on factors which influence both state taxes revenues and the efectivity of tax provisions to increase state revenues from tax sector. This research uses components on GDP, which are both from production sides and sides from expenditures. To measure the effectivity of tax provision, this analysis will uses total revenues of each tax.